A kindergarten management system with dual authentication for the city kindergarten - Yahaya, Naelah Farafisyah; Abd Warif, Nor Bakiah (2024)
School Management System is a system to organize school administration, including student and teacher data, class timetable, student’s examination result and school programs. Although the times are evolving, most of the kindergarten schools in Malaysia still use manual ways to store the data, such as storing the students’ information in excel files, and update the students’ progress in a report card. As a result, the data was easily lost and stolen. The vulnerability of the issue led to the invention of The City Kindergarten management system. The goal of this project is to create an online management system with dual authentication for The City Kindergarten’s three target users: admin, teachers, and parents. Users can use this system to register teachers and students, manage class, timetable, and events. Dual authentication used in this system are strong password and email One-Time Password (OTP) for administrators and teachers, and strong password and email verification for parents. Besides that, this system enables users of The City Kindergarten to store the data securely. The methodology used in the project is a prototype model. Programming languages used in this system are HTML, CSS, PHP, and JavaScript. Several user testing are conducted involving two sections, section A for interface and section B functionality. Based on their feedback, it can be concluded that 4 out of 5 marks has been given, and the system is functioning effectively and satisfies their requirements